Addition Of Coleus Amboinicus, L Leaf’s Extract In Ration To Percentage Of Carcass, Abdominal Fat, Liver And Heart Broiler: Bahasa Inggris - Nelzi Fati; R Siregar; Sujatmiko Sujatmiko (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
The purpose of this study was to determine the effect of giving coleus amboinicus, L leaf’s extract, on the percentage of carcass, liver, heart and abdominal fat and the level of coleus amboinicus,L extract which is appropriate in broiler feed. This research was conducted in labor and broiler enclosures of the Payakumbuh State Agricultural Polytechnic, from January to May 2018. The material was DOC, commercial food 311, corn, bran, soybean meal, fish meal and minerals, and the equipment used was cages and equipment. The design used is RAL with 6 treatments and 4 replications. The results obtained that the addition of coleus amboinicus, L extract, L did not affect significantly (P> 0.05) on the percentage of carcass and liver, while the administration of coleus amboinicus, L leaf’s extract significantly affected (P <0.05) on the percentage of heart and abdominal fat broiler. Giving a dry of coleus amboinicus leaf’s, L, 4 g / kg ration can reduce broiler abdominal fat.